Dynamic Analysis of the Guiding Shoe considering Contact Gap and Pose Disturbance - Lirong Wan; Jinwei Wang; Dejian Ma; Qingliang Zeng (Shock and Vibration)
The pose disturbance of the guide shoe under complex working conditions can lead to collision, impact, and wear failure between the guide shoe and the pin row. To explore the damage law of pose disturbance on the guiding shoe, a rigid-flexible coupling dynamic model of the walking mechanism considering the contact gap between the guiding shoe and the pin row was constructed. The contact characteristics of the guiding shoe under different poses were analyzed. The results indicate that the swing around the x-axis has the most significant impact on the guiding shoe, with stress concentration primarily occurring near the corner of the trench. The posture of swinging solely around the y-axis weakens the supporting effect of the guide shoe, resulting in stress concentration on the end face of the left side face. Swinging around the z-axis results in stress concentrations on the upper faces of the shoe. Research shows that the angular velocity of the guiding shoe around the x-axis and z-axis is highly sensitive to variations in traction speed. In addition, an increase in lateral force weakens the support effect of the guiding shoe, resulting in elevated contact force on the lower side of the guiding shoe and increased y-direction load on the walking wheel. The research results provide a reference for exploring the influence of walking unit postures on the failure of the guiding shoe and for improving shearer traction reliability.